Perlindungan Hukum terhadap Hak Milik Atas Tanah untuk Pembangunan Kepentingan Umum - Made Ayu Wangi Utari Suryatika; I Gusti Bagus Suryawan; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2020)
The role of land is very important in addition to being the capital for administering the life of the state but also the life of the people. Land function as the fulfillment of human needs in many aspects such as for housing, agriculture, plantations, and industrial activities that require the availability of land. Land has a social function, where one of the government's efforts in the context of national development is development in the public interest, such as the construction of highways, people's settlements, traditional markets, construction of mall buildings and so on. So the problem under investigation is What is the form of legal protection of land rights for the development of public interests, and how is the mechanism for compensating land rights for development of public interests. The method used is normative legal research with legislation and conceptual approaches, as well as sources of legal materials used are primary and secondary legal materials with collection techniques of library legal materials that are analyzed quantitatively in a descriptive analytical form. Based on the results of research and analysis, a conclusion can be drawn from legal protection of land rights that there are two forms of legal protection, namely preventive legal protection and repressive legal protection, in addition, Article 1 number 10 of Law No. 2 of 2012 is the basis of compensation for holders of land rights. The advice that can be delivered is that in practice the holders of land rights are often not satisfied with the compensation provided, according to which the amount of compensation is not proportional to material and material losses. Therefore, it is expected that the government as the land acquisition party applies an objective objectivity where careful consideration and calculation are carried out, so that the compensation as expected by the holder of the right to the land and even later the compensation can become compensation.